Prespektif Filsafat Kristen Tentang Eksistensi Allah - Benny Zakari; Hendri Irwansyah Zebua; Moses Lawalata (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The existence of God is something that humans have always questioned. Humans rely on reason and knowledge to find out about the existence of God, even though humans have never found certainty about the existence of God. So various human assumptions about God arose, that God never existed, and some people denied and denied the existence of God. Even though humans engage in various studies, it is impossible for humans to fully understand and know the existence of God, because God is transcendent and unlimited, while humans are immanent or limited. Therefore, in writing this article, the author looked at it from a philosophical perspective based on Christian faith to answer several questions: Is it true that God does not exist? Is God just a human imagination? Many people, especially certain groups who do not believe in the existence of God, think that anyone who believes in the existence of God is a fool. This article discusses theological concepts and Christian philosophical thought, using arguments used to prove the inseparable existence of God from the perspective of Christian faith. Philosophy has long been a means of understanding and exploring the existence of God in various Christian traditions. The author presents several philosophical arguments used by Christian theologians to support belief in the existence of God, and also discusses the contribution of thought leadership of Christian philosophers in forming views on the existence of God. From a philosophical perspective, this article offers a deeper understanding of how the Christian faith views the existence of God and how philosophy can play a role in strengthening those beliefs. Finally, this article provides an overview of how to study philosophy to understand and reflect on the existence of God, especially within the framework of Christianity.